2006
DOI: 10.3168/jds.s0022-0302(06)72075-6
|View full text |Cite
|
Sign up to set email alerts
|

Stocking Density and Feed Barrier Design Affect the Feeding and Social Behavior of Dairy Cattle

Abstract: The objectives of this study were to: 1) evaluate how stocking density at the feed bunk affects feeding and social behavior of dairy cows; and 2) determine if this effect is further influenced by the type of feed barrier used. Thirty-six lactating Holstein cows, allotted to 4 groups, were subjected to each of 4 stocking density treatments and 2 feed barrier treatments. Initially, 2 groups were assigned to a headlock barrier, and 2 groups to a post-and-rail barrier. Each group was then exposed to 4 stocking den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
234
7
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(262 citation statements)
references
References 14 publications
19
234
7
2
Order By: Relevance
“…Furthermore, the lowest average number of visits to the feeding trough found by Proudfoot et al (2009) was 23, and was recorded for multiparous cows 1 week after calving under noncompetitive feeding treatments (1 : 1 (cows : feed bin)). It has already been proven that competitive feeding situations such as a reduced feeding space per cow at the feed bunk (Huzzey et al, 2006) or a cow : feed bin ratio of 2 : 1 instead of 1 : 1 (Proudfoot et al, 2009;Harb et al, 1985) can have a reducing effect on the time spent feeding per day (min). Considering the fact that cows were housed in tie-stall barns and were fed ad libitum, the feeding situations were noncompetitive in both of the studies of Vasilatos and Wangsness (1980) and Dado and Allen (1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lowest average number of visits to the feeding trough found by Proudfoot et al (2009) was 23, and was recorded for multiparous cows 1 week after calving under noncompetitive feeding treatments (1 : 1 (cows : feed bin)). It has already been proven that competitive feeding situations such as a reduced feeding space per cow at the feed bunk (Huzzey et al, 2006) or a cow : feed bin ratio of 2 : 1 instead of 1 : 1 (Proudfoot et al, 2009;Harb et al, 1985) can have a reducing effect on the time spent feeding per day (min). Considering the fact that cows were housed in tie-stall barns and were fed ad libitum, the feeding situations were noncompetitive in both of the studies of Vasilatos and Wangsness (1980) and Dado and Allen (1994).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, an increase in interference interactions associated with feeding space restrictions has been well documented not only in confined calves and adult cattle (Olofsson, 1999;DeVries et al, 2004;Huzzey et al, 2006) but also in pastoral environments. For example, Walker and Heitschmidt (1989) reported that reductions in grazing space allowance (30 ha v. 10 ha paddocks) Table 3 Mean number of bowls visited 6 s.e.m.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was likely due to positive effects of the headlock barriers in reducing competitive interactions; there were 21% fewer displacements at the feed bunk when cows accessed feed by the headlock barrier compared with the post-and-rail barrier. Huzzey et al (2006) retested the effects of these two types of feed bunk barriers over a range of stocking densities: 0.81, 0.61, 0.41 and 0.21 m/cow (corresponding to 1.33, 1.00, 0.67 and 0.33 headlocks/cow). Daily feeding times were higher and the duration of inactive standing in the feeding area (waiting to gain access to the feed bunk) was lower when using a post-andrail compared with a headlock feed barrier.…”
Section: Physical Design Of the Feed Barriermentioning
confidence: 99%